Membership Eligibility in Companies Under OHADA Law: A Critical Appraisal - Rashma , Micheal (Journal of Global Economy, Business and Finance, 2026)
OHADA Law plays a crucial role in fostering economic growth and regional integration by harmonizing business regulations in the era of globalization and trade liberalization. This study examines the legal framework surrounding company membership under OHADA Law. While certain individuals such as legally incapacitated persons or those facing legal prohibitions cannot become company members, the law provides alternative solutions. The study explores the distinction between members and shareholders and clarifies the eligibility criteria for company membership. Using an analytical approach, this research finds that any natural or corporate entity, unless restricted by legal incapacity, prohibition, or incompatibility, can be a company member under OHADA Uniform Act. Furthermore, the law offers flexibility for incapacitated individuals by allowing legal representatives to act on their behalf.